2013
DOI: 10.5812/ircmj.13805
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Alpha Blockers in Treatment of Premature Ejaculation: A Pilot Clinical Trial

Abstract: Background:Premature ejaculation (PE) is the most common sexual disorder in men and studies reported prevalence up to 30% (1, 2). PE is not a life-threatening medical condition but it influences the quality of life (QoL).Objectives:The aim of this study was to compare the efficiency, and safety of alpha blocker drugs in the treatment of patients with premature ejaculation (PE). Additionally we investigated the quality of life (QoL) in patients with PE who were treated with alpha blocker drugs.Materials and Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 19 publications
2
20
0
2
Order By: Relevance
“…With this background, silodosin showed greater improvements in PE profiles and related symptoms along with IELT in acquired PE patients with or without ED compared with naftopidil. The present study suggested the clinical feasibility of silodosin as an alternative option for PE treatment the same as our preliminary and other studies . Additionally, current findings confirmed the roles of α1A‐AR subtypes on ejaculation, and would extend the clinical window for treatment of PE.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…With this background, silodosin showed greater improvements in PE profiles and related symptoms along with IELT in acquired PE patients with or without ED compared with naftopidil. The present study suggested the clinical feasibility of silodosin as an alternative option for PE treatment the same as our preliminary and other studies . Additionally, current findings confirmed the roles of α1A‐AR subtypes on ejaculation, and would extend the clinical window for treatment of PE.…”
Section: Discussionsupporting
confidence: 88%
“…Recent advances in pharmacological treatment for PE have provided us with new evidence regarding dapoxetine, tramadol, and lidocaine and/or prilocaine . Among these therapeutic options, α‐blockers attract attention as alternative treatment choices, because of their suppressive actions for contractions of the seminal vesicle, vas deferens and prostate, and related muscles are direct peripheral effector organs to induce projectile ejaculation . These peripheral effector organs should be considered as a new target for treating premature ejaculation.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, silodosin was more efficient and safer than the other α1 ARA (tamsulosin, alfuzosin, terazosin and doxazosin mesylate) when taken continuously during 2 weeks for the treatment of PE [30].…”
Section: F Folic Acid Supplementationmentioning
confidence: 98%
“…Multiple studies have shown the effectiveness of alpha‐1 blockers in minimizing PE . The most common alpha‐1 blockers used in the treatment of PE include tamsulosin, silodosin, terazosin and alfuzosin, with all showing a statistically significant increase in IELT . At therapeutic doses, side‐effects of alpha‐blockers are rare, but include anorgasmia, dry mouth, nasal congestion, drowsiness and orthostatic hypotension …”
Section: Current Therapiesmentioning
confidence: 99%